A novel multifunctional gold nanorod-mediated and tumor-targeted gene silencing of GPC-3 synergizes photothermal therapy for liver cancer. (5th February 2021) - Liu, Yanling; Tan, Manman; Fang, Chunjuan; Chen, Xiaoyan; Liu, Huan; Feng, Ying; Zhang, Yujuan; Min, Weiping
Abstract: Tumor-specific targeted delivery is a major obstacle to clinical treatment of hepatocellular carcinoma (HCC). Here we have developed a novel multi-functional nanostructure GAL-GNR-siGPC-3, which consists of Galactose (GAL) as the HCC-targeting moiety, golden nanorods (GNR) as a framework to destroy tumor cells under laser irradiation, and siRNA of Glypican-3 (siGPC-3) which induce specifically gene silence of GPC-3 in HCC. Glypican-3 (GPC-3) gene is highly associated with HCC and is a new potential target for HCC therapy. On the other hand, Gal can specifically bind to the asialoglycoprotein receptor which is highly expressed on membrane of hepatoma cells. GAL and siGPC-3 can induce targeted silencing of GPC-3 gene in hepatoma cells. In vivo and in vitro results showed that GAL-GNR-siGPC-3 could significantly induce downregulation of GPC-3 gene and inhibit the progression of HCC. More notably, GAL-GNR-siGPC-3 could induce both GPC-3 gene silencing and photothermal effects, and the synergistic treatment of tumors was more effective than individual treatments. In summary, GAL-GNR-siGPC-3 achieved a synergistic outcome to the treatment of cancer, which opens up a new approach for the development of clinical therapies for HCC.